Karakum desert: a unique source of cultivable novel and rare actinomycetes with a remarkable biosynthetic potential - Hayrettin Saygin; Nevzat Sahin; Michael Goodfellow (World Journal of Microbiology and Biotechnology, 2025)
A culture-based strategy was used to isolate and screen representative actinomycetes from six sampling sites in the Karakum Desert, Turkmenistan. A total of 459 actinomycete isolates were obtained using 16 selective media, and 270 representative strains were subjected to 16 S rRNA gene sequencing. Comparative 16 S rRNA gene sequence analyses on colour-group representatives led to their assignment to 17 genera with validly published names which included many isolates assigned to novel or putatively novel species including ones belonging to rare genera, such as Actinocorallia , Actinomadura , Jiangella and Nonomuraea . Mining of whole-genome sequences of 32 isolates which formed distinct lineages in phylogenomic trees revealed biosynthetic gene clusters predicted to encode for many novel specialized metabolites, notably antibiotics. The genomes of most of these isolates included genes associated with the promotion of plant growth while bioinformatic analyses of stress-related genes provided on insight into how filamentous actinomycetes have adapted to harsh environmental conditions in the Karakum Desert. This extensive bioprospecting campaign shows that the Karakum Desert is a unique source of novel, rare and gifted filamentous actinomycetes with the ability to synthesise new specialized metabolites needed to address key existential issues facing humankind, especially, the urgent need to find a new generation of therapeutic antibiotics to control multidrug-resistant microbial pathogens and compounds that protect and promote plant growth.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Atacama desert is a source of new Micromonospora strains: description of Micromonospora sicca sp. nov - Lorena Carro; Patrycja Golińska; Zaki Saati-Santamaría; José M. Igual; Hans-Peter Klenk; Michael Goodfellow (Systematic and Applied Microbiology, 2024)

Atacama desert actinomycetes: taxonomic analysis, drought tolerance and plant growth promoting potential - Feiyang Xie; Barbara Andrews; Juan A. Asenjo; Michael Goodfellow; Wasu Pathom-aree (World Journal of Microbiology and Biotechnology, 2024)

Novel species of Frankia, Frankia gtarii sp. nov. and Frankia tisai sp. nov., isolated from a root nodule of Alnus glutinosa - Imen Nouioui; Faten Ghodhbane-Gtari; Gabriele Pötter; Hans-Peter Klenk; Michael Goodfellow (Systematic and Applied Microbiology, 2023)

Actinospica acidithermotolerans sp. nov., a novel actinomycete isolated from sediment from an Indonesian hot spring - Ali B. Kusuma; Kurniawan E. Putra; Leggina R. Vanggy; Joshua Loh; Imen Nouioui; Michael Goodfellow (Archives of Microbiology, 2022)
A polyphasic study was designed to resolve the taxonomic position of isolate MGRD01-02 T which was recovered from an acidic hot spring in Indonesia and assigned to the genus Actinospica . Phylogenetic analyses based on 16S rRNA gene sequences show that the isolate is most closely related to the type strains of Actinospica acidiphila (98.5%), Actinospica robiniae (97.8%) and Actinospica durhamensis (96.8%). Morphological and chemotaxonomic data underpin the assignment of the isolate to the genus Actinospica as it forms an extensively branched substrate mycelium which carries tufts of white aerial hyphae that differentiate into straight to flexuous chains of cylindrical spores with faint rugose surfaces, contains 2,6-diamino-3-hydroxydiaminopimelic acid in the peptidoglycan, mixtures of hydrogenated menaquinones with nine isoprene units, iso- C 15:O and iso -C 16:O as major fatty acids and phosphatidylethanolamine as the diagnostic phospholipid. Whole-genome sequence analyses show that the isolate, A. durhamensis CSCA 57 T and Actinocrinis puniceicyclus DSM 45168 T have genome sizes of 7.9, 9.6 and 6.7 Mbp, respectively. A phylogenomic tree shows that they form distinct branches in a well-supported clade, a result supported by associated phenotypic data. Average nucleotide identity and digital DNA:DNA hybridization similarities are below the recommended thresholds for assigning strains to the same species; they also indicate that isolate MGRD01-02 T is most closely related to the A. durhamensis and A. robiniae strains. Corresponding amino acid identity and conserved protein data not only support these relationships but also confirm the taxonomic integrity of the genus Actinocrinis . Based on these results, it is proposed that isolate MGRD01-02 T (= CCMM B1308 T = ICEBB-09 T = NCIMB 15218 T ) be classified in the genus Actinospica as Actinospica acidithermotolerans sp. nov. The draft genome of the isolate and its closest phylogenomic neighbours contain biosynthetic gene clusters with the potential to produce new natural products, notably antibiotics.

Genome-based classification of Streptomyces pinistramenti sp. nov., a novel actinomycete isolated from a pine forest soil in Poland with a focus on its biotechnological and ecological properties - Magdalena Świecimska; Patrycja Golińska; Michael Goodfellow (Antonie van Leeuwenhoek, 2022)

Correction to: Critical Review of Exposure and Effects: Implications for Setting Regulatory Health Criteria for Ingested Copper - Alicia A. Taylor; Joyce S. Tsuji; Michael R. Garry; Margaret E. McArdle; William L. Goodfellow; William J. Adams; Charles A. Menzie (Environmental Management, 2022)

Nocardia noduli sp. nov., a novel actinobacterium with biotechnological potential - Imen Nouioui; Gabriele Pötter; Marlen Jando; Michael Goodfellow (Archives of Microbiology, 2022)
A genome-based polyphasic study was undertaken to establish the taxonomic status of an actinobacterium strain isolated from an actinorhizal root nodule. Strain ncl1 T was found to have chemotaxonomic, cultural and morphological properties characteristic of members of the genus Nocardia . The strain was closely related to Nocardia aurea in the phylogenetic trees based on 16S rRNA gene and genome sequences. The draft genome of the strain is 8.9 Mbp in size, has a genomic DNA G + C content of 67.0% and was predicted to contain at least 19 biosynthetic gene clusters encoding for specialized metabolites. Strain ncl1 T was distinguished from its closest neighbour, N. aurea DSM 103986 T , by a broad range of phenotypic properties and by low average nucleotide identity and digital DNA-DNA hybridization scores. Consequently, the strain represents a novel Nocardia species for which the name Nocardia noduli sp. nov. is proposed. The type strain is ncl1 T (CECT 30123 T = DSM 110878 T ). The present study provides further evidence that actinorhizal nodules are a source of novel species of Nocardia .

Genome-based classification of the Streptomyces violaceusniger clade and description of Streptomyces sabulosicollis sp. nov. from an Indonesian sand dune - Ali B. Kusuma; Imen Nouioui; Michael Goodfellow (Antonie van Leeuwenhoek, 2021)
A polyphasic study was designed to determine the taxonomic provenance of a strain, isolate PRKS01-29 T , recovered from an Indonesian sand dune and provisionally assigned to the Streptomyces violaceusniger clade. Genomic, genotypic and phenotypic data confirmed this classification. The isolate formed an extensively branched substrate mycelium which carried aerial hyphae that differentiated into spiral chains of rugose ornamented spores, contained LL-as the wall diaminopimelic acid, MK-9 (H 6 , H 8 ) as predominant isoprenologues, phosphatidylethanolamine as the diagnostic phospholipid and major proportions of saturated, iso - and anteiso - fatty acids. Whole-genome sequences generated for the isolate and Streptomyces albiflaviniger DSM 41598 T and Streptomyces javensis DSM 41764 T were compared with phylogenetically closely related strains, the isolate formed a branch within the S. violaceusniger clade in the resultant phylogenomic tree. Whole-genome sequences data showed that isolate PRKS01-29 T was most closely related to the S. albiflaviniger strain but was distinguished from the latter and from other members of the clade using combinations of phenotypic properties and average nucleotide identity and digital DNA:DNA hybridization scores. Consequently, it is proposed that isolate PRKS01-29 T (= CCMM B1303 T = ICEBB-02 T = NCIMB 15210 T ) should be classified in the genus Streptomyces as Streptomyces sabulosicollis sp. nov. It is also clear that streptomycetes which produce spiral chains of rugose ornamented spores form a well-defined monophyletic clade in the Streptomyces phylogenomic tree., the taxonomic status of which requires further study. The genome of the type strain of S. sabulosicollis contains biosynthetic gene clusters predicted to produce new natural products.

Critical Review of Exposure and Effects: Implications for Setting Regulatory Health Criteria for Ingested Copper - Alicia A. Taylor; Joyce S. Tsuji; Michael R. Garry; Margaret E. McArdle; William L. Goodfellow; William J. Adams; Charles A. Menzie (Environmental Management, 2020)
Decades of study indicate that copper oral exposures are typically not a human health concern. Ingesting high levels of soluble copper salts can cause acute gastrointestinal symptoms and, in uncommon cases, liver toxicity in susceptible individuals with repeated exposure. This focused toxicological review evaluated the current literature since the last comprehensive reviews (2007–2010). Our review identified limitations in the existing United States and international guidance for determining an oral reference dose (RfD) for essential metals like copper. Instead, an alternative method using categorical regression analysis to develop an optimal dose that considers deficiency, toxicity, and integrates information from human and animal studies was reviewed for interpreting an oral RfD for copper. We also considered subchronic or chronic toxicity from genetic susceptibility to copper dysregulation leading to rare occurrences of liver and other organ toxicity with elevated copper exposure. Based on this approach, an oral RfD of 0.04 mg Cu/kg/day would be protective of acute or chronic toxicity in adults and children. This RfD is also protective for possible genetic susceptibility to elevated copper exposure and allows for background dietary exposures. This dose is not intended to be protective of patients with rare genetic disorders for copper sensitivity within typical nutritional intake ranges, nor is it protective for those with excessive supplement intake. Less soluble mineral forms of copper in soil have reduced bioavailability as compared with more soluble copper in water and diet, which should be considered in using this RfD for risk assessments of copper.

New genus-specific primers for PCR identification of Rubrobacter strains - Jean Franco Castro; Imen Nouioui; Juan A. Asenjo; Barbara Andrews; Alan T. Bull; Michael Goodfellow (Antonie van Leeuwenhoek, 2019)

Saccharothrix tharensis sp. nov., an actinobacterium isolated from the Thar Desert, India - A. Ibeyaima; A. K. Singh; Rup Lal; Sanjay Gupta; Michael Goodfellow; Indira P. Sarethy (Antonie van Leeuwenhoek, 2018)

Amycolatopsis vastitatis sp. nov., an isolate from a high altitude subsurface soil on Cerro Chajnantor, northern Chile - Hamidah Idris; Imen Nouioui; Wasu Pathom-aree; Jean Franco Castro; Alan T. Bull; Barbara A. Andrews; Juan A. Asenjo; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

Preface - Alan T. Bull; Barbara A. Andrews; Cristina Dorador; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

Introducing the Atacama Desert - Alan T. Bull; Barbara A. Andrews; Cristina Dorador; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

Rare taxa and dark microbial matter: novel bioactive actinobacteria abound in Atacama Desert soils - Michael Goodfellow; Imen Nouioui; Roy Sanderson; Feiyang Xie; Alan T. Bull (Antonie van Leeuwenhoek, 2018)

Hunting for cultivable Micromonospora strains in soils of the Atacama Desert - Lorena Carro; Valeria Razmilic; Imen Nouioui; Lee Richardson; Che Pan; Patrycja Golinska; Juan A. Asenjo; Alan T. Bull; Hans-Peter Klenk; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

Formal description of Mycobacterium neglectum sp. nov. and Mycobacterium palauense sp. nov., rapidly growing actinobacteria - Imen Nouioui; Lorena Carro; Vartul Sangal; Marlen Jando; José Mariano Igual; Michael Goodfellow; Hans-Peter Klenk (Antonie van Leeuwenhoek, 2018)

High altitude, hyper-arid soils of the Central-Andes harbor mega-diverse communities of actinobacteria - Alan T. Bull; Hamidah Idris; Roy Sanderson; Juan Asenjo; Barbara Andrews; Michael Goodfellow (Extremophiles, 2018)

Streptomyces asenjonii sp. nov., isolated from hyper-arid Atacama Desert soils and emended description of Streptomyces viridosporus Pridham et al. 1958 - Michael Goodfellow; Kanungnid Busarakam; Hamidah Idris; David P. Labeda; Imen Nouioui; Roselyn Brown; Byung-Yong Kim; Maria del Carmen Montero-Calasanz; Barbara A. Andrews; Alan T. Bull (Antonie van Leeuwenhoek, 2017)

Production of 17- O -demethyl-geldanamycin, a cytotoxic ansamycin polyketide, by Streptomyces hygroscopicus DEM20745 - Aron Baksh; Bernhard Kepplinger; Hadiza A. Isah; Michael R. Probert; William Clegg; Corinne Wills; Michael Goodfellow; Jeff Errington; Nick Allenby; Michael J. Hall (Natural Product Research, 2017)

Lentzea chajnantorensis sp. nov., an actinobacterium from a very high altitude Cerro Chajnantor gravel soil in northern Chile - Hamidah Idris; Imen Nouioui; Juan A. Asenjo; Alan T. Bull; Michael Goodfellow (Antonie van Leeuwenhoek, 2017)

Actinomadura alkaliterrae sp. nov., isolated from an alkaline soil - Hilal Ay; Imen Nouioui; Maria del Carmen Montero-Calasanz; Lorena Carro; Hans-Peter Klenk; Michael Goodfellow; José M. Igual; Demet Çetin; Nevzat Şahin; Kamil Işık (Antonie van Leeuwenhoek, 2017)

Streptomyces aridus sp. nov., isolated from a high altitude Atacama Desert soil and emended description of Streptomyces noboritoensis Isono et al. 1957 - Hamidah Idris; David P. Labeda; Imen Nouioui; Jean Franco Castro; Maria del Carmen Montero-Calasanz; Alan T. Bull; Juan A. Asenjo; Michael Goodfellow (Antonie van Leeuwenhoek, 2017)

Streptacidiphilus toruniensis sp. nov., isolated from a pine forest soil - Patrycja Golinska; Hanna Dahm; Michael Goodfellow (Antonie van Leeuwenhoek, 2016)

Micromonospora yasonensis sp. nov., isolated from a Black Sea sediment - Aysel Veyisoglu; Lorena Carro; Kiymet Guven; Demet Cetin; Cathrin Spröer; Peter Schumann; Hans-Peter Klenk; Michael Goodfellow; Nevzat Sahin (Antonie van Leeuwenhoek, 2016)

Classification of thermophilic actinobacteria isolated from arid desert soils, including the description of Amycolatopsis deserti sp. nov. - Kanungnid Busarakam; Ros Brown; Alan T. Bull; Geok Yuan Annie Tan; Tiago D. Zucchi; Leonardo José da Silva; Wallace Rafael de Souza; Michael Goodfellow (Antonie van Leeuwenhoek, 2016)

Phytomonospora cypria sp. nov., isolated from soil - Nevzat Sahin; Aysel Veyisoglu; Demet Tatar; Hayrettin Saygin; Demet Cetin; Kiymet Guven; Hans-Peter Klenk; Michael Goodfellow (Antonie van Leeuwenhoek, 2015)

Erratum to: Streptomyces mangrovi sp. nov., isolated from mangrove forest sediment - Ghada Yousif; Kanungnid Busarakam; Byung-Yong Kim; Michael Goodfellow (Antonie van Leeuwenhoek, 2015)

Streptomyces mangrovi sp. nov., isolated from mangrove forest sediment - Ghada Yousif; Kanungnid Busarakam; Byung-Yong Kim; Michael Goodfellow (Antonie van Leeuwenhoek, 2015)

Actinospica durhamensis sp. nov., isolated from a spruce forest soil - Patrycja Golinska; Tiago Domingues Zucchi; Leonardo Silva; Hanna Dahm; Michael Goodfellow (Antonie van Leeuwenhoek, 2015)

Modestobacter lapidis sp. nov. and Modestobacter muralis sp. nov., isolated from a deteriorated sandstone historic building in Salamanca, Spain - Martha E. Trujillo; Michael Goodfellow; Kanungnid Busarakam; Raul Riesco (Antonie van Leeuwenhoek, 2015)

Genomic analyses confirm close relatedness between Rhodococcus defluvii and Rhodococcus equi (Rhodococcus hoagii) - Vartul Sangal; Amanda L. Jones; Michael Goodfellow; Paul A. Hoskisson; Peter Kämpfer; Iain C. Sutcliffe (Archives of Microbiology, 2015)

Analysis of novel kitasatosporae reveals significant evolutionary changes in conserved developmental genes between Kitasatospora and Streptomyces - Geneviève Girard; Joost Willemse; Hua Zhu; Dennis Claessen; Kanungnid Bukarasam; Michael Goodfellow; Gilles P. van Wezel (Antonie van Leeuwenhoek, 2014)

Erratum to: Description of Geodermatophilus amargosae sp. nov., to Accommodate the Not Validly Named Geodermatophilus obscurus subsp. amargosae (Luedemann, 1968) - Maria del Carmen Montero-Calasanz; Markus Göker; Manfred Rohde; Cathrin Spröer; Peter Schumann; Shanmugam Mayilraj; Michael Goodfellow; Hans-Peter Klenk (Current Microbiology, 2014)

Streptomyces leeuwenhoekii sp. nov., the producer of chaxalactins and chaxamycins, forms a distinct branch in Streptomyces gene trees - Kanungnid Busarakam; Alan T. Bull; Geneviève Girard; David P. Labeda; Gilles P. van Wezel; Michael Goodfellow (Antonie van Leeuwenhoek, 2014)

Description of Geodermatophilus amargosae sp. nov., to Accommodate the Not Validly Named Geodermatophilus obscurus subsp. amargosae (Luedemann, 1968) - Maria del Carmen Montero-Calasanz; Markus Göker; Manfred Rohde; Cathrin Spröer; Peter Schumann; Shanmugam Mayilraj; Michael Goodfellow; Hans-Peter Klenk (Current Microbiology, 2014)

Streptacidiphilus hamsterleyensis sp. nov., isolated from a spruce forest soil - Patrycja Golinska; Byung-Yong Kim; Hanna Dahm; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Erratum to: Streptacidiphilus durhamensis sp. nov., isolated from a spruce forest soil - Patrycja Golinska; Lina Ahmed; Dylan Wang; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Rhodococcus jostii: a home for Rhodococcus strain RHA1 - Amanda L. Jones; Julian Davies; Masao Fukuda; Roselyn Brown; Jesmine Lim; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

A new 20-membered macrolide produced by a marine-derived Micromonospora strain - Peng Fei; Wang Chuan-xi; Xie Yang; Jiang Hong-lei; Chen Lu-jie; Paulina Uribe; Alan T. Bull; Michael Goodfellow; Jiang Hong; Lian Yun-yang (Natural Product Research, 2013)

Streptacidiphilus durhamensis sp. nov., isolated from a spruce forest soil - Patrycja Golinska; Lina Ahmed; Dylan Wang; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Proposal to replace the illegitimate genus name Prescottia Jones et al. 2013 with the genus name Prescottella gen. nov. and to replace the illegitimate combination Prescottia equi Jones et al. 2013 with Prescottella equi comb. nov - Amanda L. Jones; Iain C. Sutcliffe; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Streptomyces araujoniae sp. nov.: an actinomycete isolated from a potato tubercle - Leonardo José da Silva; Rodrigo Gouvêa Taketani; Itamar Soares de Melo; Michael Goodfellow; Tiago Domingues Zucchi (Antonie van Leeuwenhoek, 2013)

Nocardia aciditolerans sp. nov., isolated from a spruce forest soil - Patrycja Golinska; Dylan Wang; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Salinispora pacifica sp. nov., an actinomycete from marine sediments - Lina Ahmed; Paul R. Jensen; Kelle C. Freel; Ros Brown; Amanda L. Jones; Byung-Yong Kim; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Prescottia equi gen. nov., comb. nov.: a new home for an old pathogen - Amanda L. Jones; Iain C. Sutcliffe; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Verrucosispora fiedleri sp. nov., an actinomycete isolated from a fjord sediment which synthesizes proximicins - Michael Goodfellow; Roselyn Brown; Lina Ahmed; Wasu Pathom-aree; Alan T. Bull; Amanda L. Jones; James E. M. Stach; Tiago Domingues Zucchi; Lixin Zhang; Jian Wang (Antonie van Leeuwenhoek, 2013)

Streptomyces bullii sp. nov., isolated from a hyper-arid Atacama Desert soil - Rakesh Santhanam; Xiaoying Rong; Ying Huang; Barbara A. Andrews; Juan A. Asenjo; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Streptomyces erringtonii sp. nov. and Streptomyces kaempferi sp. nov., isolated from a hay meadow soil - Rakesh Santhanam; Xiaoying Rong; Ying Huang; Michael Goodfellow (Antonie van Leeuwenhoek, 2013)

Erratum to: A call to arms for systematists: revitalising the purpose and practises underpinning the description of novel microbial taxa - Iain C. Sutcliffe; Martha E. Trujillo; Michael Goodfellow (Antonie van Leeuwenhoek, 2012)

Streptosporangium anatoliense sp. nov., isolated from soil in Turkey - Anil Sazak; Nevzat Sahin; Mustafa Camas; Kiymet Guven; Demet Cetin; Michael Goodfellow (Antonie van Leeuwenhoek, 2012)

Amycolatopsis bartoniae sp. nov. and Amycolatopsis bullii sp. nov., mesophilic actinomycetes isolated from arid Australian soils - Tiago Domingues Zucchi; Avinash Naga Venkata Bonda; Sarah Frank; Byung-Yong Kim; Jenileima Devi Kshetrimayum; Michael Goodfellow (Antonie van Leeuwenhoek, 2012)

Verrucosispora wenchangensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Hai-peng Lin; Lei Li; Roselyn Brown; Michael Goodfellow; Zixin Deng; Kui Hong (Antonie van Leeuwenhoek, 2012)

Streptomyces deserti sp. nov., isolated from hyper-arid Atacama Desert soil - Rakesh Santhanam; Chinyere K. Okoro; Xiaoying Rong; Ying Huang; Alan T. Bull; Barbara A. Andrews; Juan A. Asenjo; Hang-Yeon Weon; Michael Goodfellow (Antonie van Leeuwenhoek, 2012)

The BISMiS 2011 special issue on prokaryotic systematics, a vital discipline entering a period of transition - Iain C. Sutcliffe; Martha E. Trujillo; Michael Goodfellow (Antonie van Leeuwenhoek, 2012)

A call to arms for systematists: revitalising the purpose and practises underpinning the description of novel microbial taxa - Iain C. Sutcliffe; Martha E. Trujillo; Michael Goodfellow (Antonie van Leeuwenhoek, 2012)

Verrucosispora maris sp. nov., a novel deep-sea actinomycete isolated from a marine sediment which produces abyssomicins - Michael Goodfellow; James E. M. Stach; Roselyn Brown; Avinash Naga Venkata Bonda; Amanda L. Jones; Joanne Mexson; Hans-Peter Fiedler; Tiago Domingues Zucchi; Alan T. Bull (Antonie van Leeuwenhoek, 2012)

Genus-specific primers targeting the 16S rRNA gene for PCR detection of members of the genus Verrucosispora - Qingyi Xie; Kui Hong; Michael Goodfellow (Antonie van Leeuwenhoek, 2011)

A guide to successful bioprospecting: informed by actinobacterial systematics - Michael Goodfellow; Hans-Peter Fiedler (Antonie van Leeuwenhoek, 2010)

Computer-assisted numerical analysis of colour-group data for dereplication of streptomycetes for bioprospecting and ecological purposes - Sanjay Antony-Babu; James E. M. Stach; Michael Goodfellow (Antonie van Leeuwenhoek, 2010)

Diversity of culturable actinomycetes in hyper-arid soils of the Atacama Desert, Chile - Chinyere K. Okoro; Roselyn Brown; Amanda L. Jones; Barbara A. Andrews; Juan A. Asenjo; Michael Goodfellow; Alan T. Bull (Antonie van Leeuwenhoek, 2009)

Biosystematics of alkaliphilic streptomycetes isolated from seven locations across a beach and dune sand system - Sanjay Antony-Babu; Michael Goodfellow (Antonie van Leeuwenhoek, 2008)

Individual Variation in 3-Methylbutanal: A Putative Link between Human Leukocyte Antigen and Skin Microflora - Sergey U. Savelev; Sanjay Antony-Babu; S. Craig Roberts; Huitu Wang; Anthony S. Clare; L. Morris Gosling; Marion Petrie; Michael Goodfellow; Anthony G. O’Donnell; Alan C. Ward (Journal of Chemical Ecology, 2008)

Characterisation of micromonosporae from aquatic environments using molecular taxonomic methods - Luis A. Maldonado; James E. M. Stach; Alan C. Ward; Alan T. Bull; Michael Goodfellow (Antonie van Leeuwenhoek, 2008)

Genetic and phenotypic evidence for Streptomyces griseus ecovars isolated from a beach and dune sand system - Sanjay Antony-Babu; James E. M. Stach; Michael Goodfellow (Antonie van Leeuwenhoek, 2008)

Streptomyces sudanensis sp. nov., a new pathogen isolated from patients with actinomycetoma - Erika T. Quintana; Katarzyna Wierzbicka; Pawel Mackiewicz; Abdalla Osman; Ahmed H. Fahal; Mohamed E. Hamid; Jolanta Zakrzewska-Czerwinska; Luis A. Maldonado; Michael Goodfellow (Antonie van Leeuwenhoek, 2008)

The Streptomyces violaceusniger clade: a home for streptomycetes with rugose ornamented spores - Michael Goodfellow; Yashawant Kumar; David P. Labeda; Langkah Sembiring (Antonie van Leeuwenhoek, 2007)

Nonomuraea aegyptia sp. nov., a novel actinomycete isolated from a sand dune - Wael N. Hozzein; Michael Goodfellow (Antonie van Leeuwenhoek, 2007)

Diversity of actinomycetes isolated from Challenger Deep sediment (10,898 m) from the Mariana Trench - Wasu Pathom-aree; James E. M. Stach; Alan C. Ward; Koki Horikoshi; Alan T. Bull; Michael Goodfellow (Extremophiles, 2006)

Erratum - Alan T. Bull; James E. M. Stach; Alan C. Ward; Michael Goodfellow (Antonie van Leeuwenhoek, 2005)

Marine actinobacteria: perspectives, challenges, future directions - Alan T Bull; James E.M Stach; Alan C Ward; Michael Goodfellow (Antonie van Leeuwenhoek, 2005)

Diversity of cultivable actinobacteria in geographically widespread marine sediments - Luis A. Maldonado; James E.M. Stach; Wasu Pathom-aree; Alan C. Ward; Alan T. Bull; Michael Goodfellow (Antonie van Leeuwenhoek, 2005)

Editorial - Alan Bull; Michael Goodfellow (Antonie van Leeuwenhoek, 2005)

Marine actinomycetes as a source of novel secondary metabolites - Hans-Peter Fiedler; Christina Bruntner; Alan T. Bull; Alan C. Ward; Michael Goodfellow; Olivier Potterat; Carsten Puder; Gerhard Mihm (Antonie van Leeuwenhoek, 2005)

Streptacidiphilus jiangxiensis sp. nov., a novel actinomycete isolated from acidic rhizosphere soil in China - Ying Huang; Quingfeng Cui; Liming Wang; Carlos Rodriguez; Erika Quintana; Michael Goodfellow; Zhiheng Liu (Antonie van Leeuwenhoek, 2004)

Rapid determination of vapA/vapB genotype in Rhodococcus equi using a differential polymerase chain reaction method - Christopher Oldfield; Hal Bonella; Lynne Renwick; Hilary I. Dodson; Grace Alderson; Michael Goodfellow (Antonie van Leeuwenhoek, 2004)

New primers for the class Actinobacteria : application to marine and terrestrial environments - James E. M. Stach; Luis A. Maldonado; Alan C. Ward; Michael Goodfellow; Alan T. Bull (Environmental Microbiology, 2003)
Summary In this study, we redesigned and evaluated primers for the class Actinobacteria . In silico testing showed that the primers had a perfect match with 82% of genera in the class Actinobacteria , representing a 26–213% improvement over previously reported primers. Only 4% of genera that displayed mismatches did so in the terminal three bases of the 3′ end, which is most critical for polymerase chain reaction success. The primers, designated S‐C‐Act‐0235‐a‐S‐20 and S‐C‐Act‐0878‐a‐A‐19, amplified an ≈ 640 bp stretch of the 16S rRNA gene from all actinobacteria tested (except Rubrobacter radiotolerans ) up to an annealing temperature of 72°C. An Actinobacteria Amplification Resource ( http://microbe2.ncl.ac.uk/MMB/AAR.htm ) was generated to provide a visual guide to aid the amplification of actinobacterial 16S rDNA. Application of the primers to DNA extracted from marine and terrestrial samples revealed the presence of actinobacteria that have not been described previously. The use of 16S rDNA similarity and DNA–DNA pairing correlations showed that almost every actinomycete clone represented either a new species or a novel genus. The results of this study reinforce the proposition that current culture‐based techniques drastically underestimate the diversity of Actinobacteria in the environment and highlight the need to evaluate taxon‐specific primers regularly in line with improvements in databases holding 16S rDNA sequences.

Nonomuraea terrinata sp. nov., a novel soil actinomycete - Erika Quintana; Luis Maldonado; Michael Goodfellow (Antonie van Leeuwenhoek, 2003)

Numerical phenetic classification of clinically significant aerobic sporoactinomycetes and related organisms - Martha E. Trujillo; Michael Goodfellow (Antonie van Leeuwenhoek, 2003)

Classification of novel soil streptomycetes as Streptomyces aureus sp. nov., Streptomyces laceyi sp. nov. and Streptomyces sanglieri sp. nov. - Gilson Paulo Manfio; Ekrem Atalan; Jolanta Zakrzewska – Czerwinska; Marian Mordarski; Carlos Rodríguez; Matthew David Collins; Michael Goodfellow (Antonie van Leeuwenhoek, 2003)

Streptacidiphilus gen. nov., acidophilic actinomycetes with wall chemotype I and emendation of the family Streptomycetaceae (Waksman and Henrici (1943)AL) emend. Rainey et al. 1997 - Seung Bum Kim; John Lonsdale; Chi-Nam Seong; Michael Goodfellow (Antonie van Leeuwenhoek, 2003)

Gordonia sinesedis sp. nov., a novel soil isolate - Luis A. Maldonado; Fiona M. Stainsby; Alan C. Ward; Michael Goodfellow (Antonie van Leeuwenhoek, 2003)

Streptomyces yatensis sp. nov., a novel bioactive streptomycete isolated from a New-Caledonian ultramafic soil - Danielle Saintpierre; Hamid Amir; René Pineau; Langkah Sembiring; Michael Goodfellow (Antonie van Leeuwenhoek, 2003)

Genomic and phenomic differentiation of Rhodococcus equi and related strains - Elizabeth J. McMinn; Grace Alderson; Hilary I. Dodson; Michael Goodfellow; Alan C. Ward (Antonie van Leeuwenhoek, 2000)

The Nocardia salmonicida clade, including descriptions of Nocardia cummidelens sp. nov., Nocardia fluminea sp. nov. and Nocardia soli sp. nov. - Luis Maldonado; John V. Hookey; Alan C. Ward; Michael Goodfellow (Antonie van Leeuwenhoek, 2000)

Selective isolation and characterisation of members of the Streptomyces violaceusniger clade associated with the roots of Paraserianthes falcataria - Langkah Sembiring; Alan C. Ward; Michael Goodfellow (Antonie van Leeuwenhoek, 2000)

A whole-genome radiation hybrid panel and framework map of the rat genome - Linda C. McCarthy; Marie-Therese Bihoreau; Susanna L. Kiguwa; Julie Browne; Takeshi K. Watanabe; Haretsugu Hishigaki; Atsushi Tsuji; Susanne Kiel; Caleb Webber; Maria E. Davis; Catherine Knights; Angela Smith; et al. (Mammalian Genome, 2000)

Biosystematic studies on novel streptomycetes from soil - Ekrem Atalan; Gilson Paulo Manfio; Alan C. Ward; Reiner M. Kroppenstedt; Michael Goodfellow (Antonie van Leeuwenhoek, 2000)

Rapid characterisation of deep-sea actinomycetes for biotechnology screening programmes - Joy A. Colquhoun; Joseph Zulu; Michael Goodfellow; Koki Horikoshi; Alan C. Ward; Alan T. Bull (Antonie van Leeuwenhoek, 2000)

Sequence analysis of 16S rRNA genes amplified from two ribosomal RNA gene clusters of Bifidobacterium bifidum - Jung-Hoon Yoon; Dong Koo Yim; Michael Goodfellow; Yong-Ha Park (Antonie van Leeuwenhoek, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Novel rhodococci and other mycolate actinomycetes from the deep sea - Joy A. Colquhoun; Joanne Mexson; Michael Goodfellow; Alan C. Ward; Koki Horikoshi; Alan T. Bull (Antonie van Leeuwenhoek, 1998)

Rhodococcal systematics: problems and developments - Michael Goodfellow; Grace Alderson; Jongsik Chun (Antonie van Leeuwenhoek, 1998)

Numerical and chemical classification ofStreptosporangium and some related actinomycetes - Timothy S. Whitham; Medha Athalye; David E. Minnikin; Michael Goodfellow (Antonie van Leeuwenhoek, 1994)

Biosystematics and diversity amongst novel carboxydotrophic actinomycetes - Anthony G. O'Donnell; Christine Falconer; Michael Goodfellow; Alan C. Ward; Edwin Williams (Antonie van Leeuwenhoek, 1994)

Suprageneric classification of peptidoglycan group B actinomycetes by nucleotide sequencing of 5S ribosomal RNA - Yong-Ha Park; Ken-Ichiro Suzuki; Dong-Gu Yim; Keun-Chul Lee; Eundooj Kim; Jun-sik Yoon; Sung-jun Kim; Yong-Hee Kho; Michael Goodfellow; Kazuo Komagata (Antonie van Leeuwenhoek, 1994)

Editorial - Michael Goodfellow (Antonie van Leeuwenhoek, 1994)

Mycolic acid patterns of some species of Mycobacterium - David E. Minnikin; S. Megan Minnikin; James H. Parlett; Michael Goodfellow; Mogens Magnusson (Archives of Microbiology, 1984)

Lipids in the classification of Nocardioides: Reclassification of Arthrobacter simplex (Jensen) lochhead in the genus Nocardioides (Prauser) emend. O'Donnell et al. as Nocardioides simplex comb. nov. - Anthony G. O'Donnell; Michael Goodfellow; David E. Minnikin (Archives of Microbiology, 1982)